2014
DOI: 10.3109/02656736.2014.906048
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of reference genes for human chondrocytes cultured in several different thermal environments

Abstract: The combination of RPL13a and YWHAZ might be suitable as reference genes for human chondrocytes cultured at 32 °C, 37 °C, and 41 °C in monolayer, pellet, or combined cultures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Analyzing HKG in colon and liver tissues from CRC patients with hepatic metastases, Blanquicett et al (2002) observed that ribosomal HKG displayed the most stable expression while those involved in metabolic pathways were the least stable ones. Substantiating the notion, we and others (Dydensborg et al 2006; Bakhashab et al 2014; Jacobsen et al 2014) demonstrated superior stability of RPLP0 and Bian et al (2015), Powell et al (2014), and Ito et al (2014) that of another ribosomal protein— RPL13A . In turn, PGK1 was one of the least stable genes in our study, although GAPDH , encoding an enzyme involved in the same metabolic pathway, performed well.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Analyzing HKG in colon and liver tissues from CRC patients with hepatic metastases, Blanquicett et al (2002) observed that ribosomal HKG displayed the most stable expression while those involved in metabolic pathways were the least stable ones. Substantiating the notion, we and others (Dydensborg et al 2006; Bakhashab et al 2014; Jacobsen et al 2014) demonstrated superior stability of RPLP0 and Bian et al (2015), Powell et al (2014), and Ito et al (2014) that of another ribosomal protein— RPL13A . In turn, PGK1 was one of the least stable genes in our study, although GAPDH , encoding an enzyme involved in the same metabolic pathway, performed well.…”
Section: Discussionmentioning
confidence: 59%
“…Yet, with stability of its expression being suboptimal, it could affect the statistical outcome. Of note, preservation of GAPDH expression upon altered conditions has been reported for human umbical vein endothelial cells (HUVECs) grown under hyperglycemic conditions (Bakhashab et al 2014), chondrocytes cultured at different temperatures (Ito et al 2014) or blood cells subjected to radiation (Vaiphei et al 2015). …”
Section: Discussionmentioning
confidence: 99%
“…The data obtained by real-time PCR were analyzed by the comparative threshold cycle method. Briefly, the target gene quantity was normalized to that of RPL13a and YWHAZ , which are known to be stable under different thermal environments [ 37 ]. The mean value of the calibration sample (the cells cultured in monolayer at 32°C) was set to 1 and the values obtained for each of the other conditions were calculated relative to that of the calibration sample.…”
Section: Methodsmentioning
confidence: 99%
“…The data obtained by qRT‐PCR were analyzed using the comparative threshold cycle method. Briefly, the quantity of the target genes was normalized to the expression levels of RPL13a and YWHAZ , which have been proven to be stable under different thermal conditions . The value of the calibration sample (cells cultured at 32°C on day 3) was set to 1, and the values for the other conditions were reported relative to that of the calibration sample.…”
Section: Methodsmentioning
confidence: 99%